Preparation and Analysis of the Profit and Loss Statement of Kiosk Rice Raihan - Putri, Nurhadini (Operations Research: International Conference Series, 2021)
MSMEs (Micro, Small and Medium Enterprises) are productive businesses owned by individuals and business entities that have met the criteria as micro-enterprises. MSMEs are one of the boosters of the country's economic conditions. So the effectiveness of MSME management must be good, but not all MSMEs understand and are able to make financial reports that can be used as guidelines for sales considerations. This makes it difficult for these MSMEs to assess whether their sales are good or not. The purpose of making this financial report is to help with financial details and analyze the ability of a rice kiosk to generate profits. Financial data analysis was carried out from the Raihan Rice Kiosk in the Griya Bandung Indah Complex, Bandung Regency. The data taken are in the form of 2 important elements, namely income and expenses which are then used vertical, horizontal and ratio analysis (Gross Profit Margin Ratio and Net Profit Margin Ratio) to determine the level of management effectiveness. The results obtained are the management of rice sales carried out during this period is classified as good for the MSME group. This can be seen from the increase in profit and the percentage ratio of GPM (ranging at 26%) and NPM (ranging at 17%). With the preparation of this financial report, it is hoped that it can help Raihan Rice Kiosks in seeing the effectiveness of sales management and can be a benchmark for future performance.